Evaluating Perceptions of Ethics Risk in a South African Government Organisation: Array - Ferreira, Sune; Mokoke, Ntombi; Mokatsanyane, Danny (Acta Universitatis Danubius. Administratio, 2021)
Unethical behaviour in South African (SA) government organisations is often highlighted in government reports as a root cause to impeding good governance and promoting integrity. While scholars have noted the conceptual overlap between ethics and leadership, there has been an inadequate investigation of the empirical relationships between ethics and risk management, as well as limited research on ethics management in SA government organisations. This study employed a quantitative research approach, where secondary data via a cross-sectional survey was used to gather the data and to achieve the research objectives. Due to limited research conducted on ethics management in SA government organisations, this research can aid in setting the basis for other possible future research.